Entry regulation as a barrier to entrepreneurship - Klapper, Leora; Laeven, Luc; Rajan, Raghuram (Journal of Financial Economics, 2006)
Using a comprehensive database of European firms, we study the effect of market entry regulations on the creation of new limited-liability firms, the average size of entrants, and the growth of incumbent firms. We find that costly regulations hamper the creation of new firms, especially in industries that should naturally have high entry. These regulations also force new entrants to be larger and cause incumbent firms in naturally high-entry industries to grow more slowly. Our results hold even when we correct for the availability of financing, the degree of protection of intellectual property, and labor regulations.